CHILDREN SCIENCE CENTER - Nobela, Galuh Rizka Fitri; Nurhamsyah, Muhammad; Gultom, Bontor Jumaylinda (JMARS: Jurnal Mosaik Arsitektur, 2022)
Science is a very important science for children to understand, because children are a golden age phase where at their age their brains grow and develop rapidly. The need to learn science from an early age is to avoid their fear in adulthood when it comes to studying science. Many children or teenagers avoid science lessons because for them it is a difficult lesson to understand. Therefore, it is necessary to learn science from an early age to avoid the stereotype that says science is difficult and scary. The Children Science Center was built to help children learn science. The Children Science Center was also built to be a means of learning science outside of school, because many schools in Indonesia have inadequate facilities for studying science. The method used in the Children Science Center is the design method of J.C Jones. Jones started his design from an idea that was equipped with information to strengthen the idea. All information is analyzed, then synthesized to produce certain concepts according to the initial idea and then evaluated. The evaluation stage will be the basis for optimizing the design. This Science Center has a commercial area and is a public space that can provide income and educational recreation for children.